Sistem Penunjang Keputusan Penentuan Reward Bagi Mitra Terbaik Menggunakan Metode Simple Additive Weighting (SAW) (Studi Kasus : PT. Telkom Akses) - Fandi Azis; A. Sidiq Purnomo (JURNAL FASILKOM (teknologi inFormASi dan ILmu KOMputer), 2021)
In the development of the world of work, a reward is an important factor to improve the quality of human resources as well as an appreciation for those with enhancement. Therefore, a company should be careful in performing its assessment. Thus, a decision support system application is required to assist a company in performing the assessment process. Accordingly, the decision-making process uses the Simple Additive Weighting (SAW) method. Results of the system functionality can run 100% well and as needed, and the result of the system accuracy test are 100%. This indicates that a decision support system can function properly with the Simple Additive Weighting (SAW) method. Keywords: Reward, Simple Additive Weighting (SAW), Decision Support System